Morphology, morphometrics, and molecular characteristics of Apis cerana and Apis nigrocincta from Central Sulawesi, Indonesia - Nuraini Nuraini; Hari Purwanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Systematics of honey bees has developed rapidly. Several studies have attempted to infer the kinship between each group of honey bees.ÃÂ One approach is the use identification and phylogenetic analysis using combination of morphology, morphometric, and molecular characteristics data. There are three species of honey bees found in the Central Sulawesi, namely Apis dorsata, A. cerana and A. nigrocincta. The last two species mentioned have similar biological properties, so they present some difficulties to identify especially with morphological characters only. The results showed that the two Apis bee species analyzed in this study, had similar morphological features compared to specimens of the same species from the other regions, whereas the morphometry of the two had variations in size compared to the same species that have been reported in other regions. The variations in the size or morphometric character of worker bees, both those with a larger or smaller size, possibly being a form of morphological adaptation to different environmental conditions. The CO1 and 16S Mitochondrial DNA sequencesof A. cerana and A. nigrocincta from this studywere similarto thesequences of the same species in the GeneBankÃ¢â¬â¢s database. This study provide preliminary data contributing to the preservation and utilization of one of IndonesiaÃ¢â¬â¢s important biodiversity resources.